2006
DOI: 10.1677/erc.1.01048
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of type 2 3α-hydroxysteroid dehydrogenase/type 5 17β-hydroxysteroid dehydrogenase (AKR1C3) and its relationship with androgen receptor in prostate carcinoma

Abstract: Type 2 3a-hydroxysteroid dehydrogenase (3a-HSD) is a multi-functional enzyme that possesses 3a-, 17b-and 20a-HSD, as well as prostaglandin (PG) F synthase activities and catalyzes androgen, estrogen, progestin and PG metabolism. Type 2 3a-HSD was cloned from human prostate, is a member of the aldo-keto reductase (AKR) superfamily and was named AKR1C3. In androgen target tissues such as the prostate, AKR1C3 catalyzes the conversion of D 4 -androstene-3,17-dione to testosterone, 5a-dihydrotestosterone to 5a-andr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
88
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 31 publications
8
88
0
Order By: Relevance
“…It has previously been shown that mRNA levels of the enzymes are correlated with protein amounts and activities in other studies [46][47][48][49][50] so we did not repeat these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been shown that mRNA levels of the enzymes are correlated with protein amounts and activities in other studies [46][47][48][49][50] so we did not repeat these studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are several enzymes which are involved in intracellular testosterone synthesis in the prostate cancer cell (25,(36)(37)(38)(39). HSD3B2 catalyzes the conversion of dehydroepi-androsterone (DHEA) to androstenedione [25,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports and our results revealed that 17-HSD5 (known as AKR1C3) positive cases were significantly associated with clinical stage. [37,38] Fung et al revealed that elevated expression of AKR1C3 is highly associated with prostate cancer. [37] We also revealed that both AR and androgen-converting enzymes were up-regulated in the highgrade or advanced prostate cancer.…”
Section: Prostate Cancer Aggressiveness and The Androgen Milieu In Thmentioning
confidence: 99%
“…[37,38] Fung et al revealed that elevated expression of AKR1C3 is highly associated with prostate cancer. [37] We also revealed that both AR and androgen-converting enzymes were up-regulated in the highgrade or advanced prostate cancer. [38] AKR1C3 (17-HSD5) may be involved in increasing the local concentration of testosterone in prostate cancer tissues, resulting in the progression, invasion and further development of prostate cancer following ADT.…”
Section: Prostate Cancer Aggressiveness and The Androgen Milieu In Thmentioning
confidence: 99%